Pengaruh Lifestyle, Modernitas dan Kontrol Diri terhadap Perilaku Konsumsi Generasi Z Kota Pekalongan dalam Pembelian Merchandise K-Pop - Ratna Firdiyana; Dwi Novaria Misidawati (Universitas 45 Surabaya, 2024)
Consumption behavior is an activity directly related to achieving, using and paying for goods or services and products needed before and after these actions. This study aims to determine the effect of lifestyle, modernity and self-control on the consumption behavior of generation Z of Pekalongan City in purchasing K-Pop merchandise. This research is a type of field research using a quantitative approach. Data collection in the study used to questionnaire method distributed directly to respondents with a sample size of 97 people. The sampling techniqueused was accidental sampling. This study used data analysis method validity test, reliability test, classical assumption test, multiple linear regression test and hypothesis testing using the IBM SPSS statistics 20 application. The result showed that partially the lifestyle variable had a positive and significant effect on consumption behavior. Modernity partially has a positive and significant effect on consumption behavior. Self-control partially has a positive and significant effect on consumption behavior. Simultaneously, lifestyle variable, modernity and self-control affect consumption behavior with a contribution value of 58.3% and the rest is influenced by other variables outside the study by 41,7%.